Sitagliptin added to stable insulin therapy with or without metformin in Chinese patients with type 2 diabetes. Issue 3 (9th December 2016) - Shankar, R Ravi; Bao, Yuqian; Han, Ping; Hu, Ji; Ma, Jianhua; Peng, Yongde; Wu, Fan; Xu, Lei; Engel, Samuel S; Jia, Weiping
Abstract: Introduction: We evaluated the tolerability and efficacy of the addition of sitagliptin in Chinese patients with type 2 diabetes mellitus receiving stable insulin therapy alone or in combination with metformin. Materials and Methods: A total of 467 patients with inadequate glycemic control on insulin (glycated hemoglobin [HbA1c] ≥7.5% and ≤11%) were randomized 1:1 to receive sitagliptin 100 mg once daily or a matching placebo for 24 weeks. Randomization was stratified based on metformin use (on or not on metformin) and type of insulin (pre‐mixed vs intermediate‐/long‐acting) at screening. The primary end‐point was the change from baseline at week 24 in HbA1c. Results: The addition of sitagliptin led to a significantly ( P < 0.001) greater week 24 HbA1c reduction (0.7%) compared with the reduction (0.3%) with placebo. A significantly ( P = 0.013) greater proportion of patients taking sitagliptin (16%) had an HbA1c of <7.0% at week 24 compared with placebo (8%). The addition of sitagliptin significantly ( P < 0.001) reduced 2‐h post‐meal glucose by 26.5 mg/dL (1.5 mmol/L) relative to placebo. Reductions from baseline in fasting plasma glucose were observed in both the sitagliptin (14.4 mg/dL reduction) and placebo (10.7 mg/dL reduction) groups; the between‐group difference was not significant. A total of 64 (27.4%) patients taking sitagliptin and 51 (21.9%) taking placebo experienced adverse events of hypoglycemia (symptomatic or asymptomatic). Neither group had a significant change from baseline in bodyweight. Conclusions: After 24 weeks, sitagliptin added to stable insulin therapy (±metformin) was generally well tolerated and improved glycemic control in Chinese patients with type 2 diabetes mellitus. Abstract : At 24 weeks, the addition of sitagliptin led to a significantly ( P < 0.001) greater HbA1c reduction (0.7%) compared with the reduction (0.3%) with placebo. A significantly ( P = 0.013) greater proportion of patients on sitagliptin (16%) had an HbA1c of <7.0% at Week 24 compared with placebo (8%). In this 24‐week study, the addition of sitagliptin to ongoing, stable‐dose insulin therapy with or without metformin improved glycemic control and was generally well‐tolerated in Chinese patients with type 2 diabetes mellitus (clinicaltrials.gov: NCT01590797).